PRILAKU MENYIMPANG REMAJA DI WARUNG REMANG-REMANG PERBATASAAN JALAN LINTAS SUMATERA BARAT-RIAU - Siti Aulia Dewi Amir; Reska Nanda R (Ensiklopedia of Journal, 2020)
The existence of escort booth in West Sumatera-Riau Border By-pass Kenagarian Tanjung Balit Kabupaten Lima Puluh Kota is giving a major effect to the teenager deviant behaviour. So there are some deviant bahaviours happen at escort booth in Kenagarian Tanjung Balit. The type of this research was qualitative with descriptive method. In this research, the data gathering which were used by researcher were observation, interview, and documentation. Based on the observation, interview with the source of the research, so the result of the research showed that (1) form of deviant behaviour in West Sumatera-Riau Border By-pass Escort Booth Kenagarian Tanjung Balit Kabupaten Lima Puluh Kota such as (a) gambling (b) fighting (c) alcoholic drinking (d) prostitution/free sex. (2) the government efford against deviant behaviour in West Sumatera-Riau Border By-pass Escort Booth Kenagarian Tanjung Balit Kabupaten Lima Puluh Kota such as (a) preventive actions with morale tuition early, compiled government ordinance for the penalty by teenager (b) law enforcement with giving penalty such as mores penalty or government administrative penalty (c) curative actions with publisher by Nagari Government with Sector Government and Police.Keywords:  Adolescent, Deviant Behavior